Exploring cultural tourism potential in Adamawa State Nigeria: a case of Mubi town - Abdullahi, Hashim; Asmawi, M Zainora; Abdul Aziz, Abdul Razak (Lomaka & Romina Publisher, 2023)
Cultural tourism plays a vital role globally. The study aims to appraise cultural tourism potential in Mubi town, Adamawa state, Nigeria. The study employed Arc. GIS.10.3 and remote sensing for location map generation. Data was generated from one hundred structured questionnaires using systematic random sampling techniques. Descriptive statistics were utilized for correlating the cultural tourism potentials (CTP) and tourism industry management (TIM). Spearman ranking techniques were used for the respondents' perception scores. The results indicated a correlation between cultural tourism potentials (CTP) and tourism industry management (TIM) and tested for reliability. The results uncovered a very significant connection between the variables at (0.01, 2-Tailed). This showed cultural tourism potential depends on effective management. Additionally, the respondents ranking depicted that horse riding maintained the highest because of its significance in the culture of northern Nigerians, Sallah of Both Eidl Fitr and Adha celebrations recorded the second position, while traditional housing, local wrestling, and Mauludul Rasul all received significant responses as a very important cultural tourism attraction in the Mubi. Recommendations on accommodations, food, and beverages are essential to be upgraded. Government and private bodies are to form a partnership. Educational awareness campaigns through seminars, workshops, and conferences are highly recommended.